2021
DOI: 10.1080/2162402x.2021.1924492
|View full text |Cite
|
Sign up to set email alerts
|

The immune microenvironment and relation to outcome in patients with advanced breast cancer treated with docetaxel with or without gemcitabine

Abstract: Preclinical studies suggest that some effects of conventional chemotherapy, and in particular, gemcitabine, are mediated through enhanced antitumor immune responses. The objective of this study was to use material from a randomized clinical trial to evaluate whether patients with preexisting immune infiltrates responded better to treatment with gemcitabine + docetaxel (GD) compared to docetaxel alone. Formalin fixed, paraffin-embedded breast cancer tissues from SBG0102 phase 3 trial patients randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…[26][27][28] Of significance, multiple studies have reported the abilities of PAFR antagonists to control the growth of cancer cells or augment the responses of therapeutic agents. 26,29,30 Given that gemcitabine chemotherapy used against multiple human malignancies either alone or in combination with other agents, exhibits adverse effects, including skin rash/necrosis, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] our current studies sought to determine the potential role of MVP release in the pathologic effects of topical gemcitabine application. To that end, pharmacologic approaches using human skin explants and genetic approaches using murine skin were used as relevant models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Of significance, multiple studies have reported the abilities of PAFR antagonists to control the growth of cancer cells or augment the responses of therapeutic agents. 26,29,30 Given that gemcitabine chemotherapy used against multiple human malignancies either alone or in combination with other agents, exhibits adverse effects, including skin rash/necrosis, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] our current studies sought to determine the potential role of MVP release in the pathologic effects of topical gemcitabine application. To that end, pharmacologic approaches using human skin explants and genetic approaches using murine skin were used as relevant models.…”
Section: Discussionmentioning
confidence: 99%
“…However, often these drugs are associated with adverse side effects, including localized skin eruptions and necrosis as well as systemic pathologies, including ototoxicity and neutropenia 6–11 . Gemcitabine is one of the commonly used chemotherapy drugs, which has been used either alone, or in combination with other antineoplastic agents for the treatment of malignancies, including pancreatic cancer, non‐small cell lung cancer, intrahepatic cholangiocarcinoma, colorectal cancer, ovarian cancer, breast cancer, and melanoma 12–18 . Nevertheless, the development of tumor resistance mechanisms to gemcitabine therapy remained one of the ongoing challenges in its limited therapeutic efficacy 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Neither of these studies have been able to explain why pre-NACT TILs were exclusively linked to pCR in TNBC [ 33 , 34 ]. A prominent inflammatory infiltrate is a well-known feature of TNBC [ 36 , 37 ]. To confirm whether the observed significance was due to the molecular subtype itself or it is linked to the density of TILs, we used logistic regression and a significant association between pCR, and TNBC subtype was confirmed irrelevant to TILs.…”
Section: Discussionmentioning
confidence: 99%
“…Each case was represented by 2–3 cores, measuring 2 mm in diameter, with the full trial cohort spread over 24 tissue microarray blocks. Tissue microarray slides were created by sectioning at 4 µm and staining with hematoxylin and eosin (H&E) or by immunohistochemistry (IHC) for CD8 (1:50, mouse monoclonal, clone C8/144B, Agilent Technologies, Santa Clara, CA, USA), FOXP3 (1:20, mouse monoclonal, clone 236A/E7, Abcam, Cambridge, UK), LAG-3 (1:100, mouse monoclonal, clone 17B4, Abcam, Cambridge, UK), PD-1 (mouse monoclonal, clone NAT105, Cell Marque, Rocklin, CA, USA), and PD-L1 (1:100, rabbit monoclonal, clone SP142, Roche Diagnostics, Laval, QC, Canada) as previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…All biomarkers except for PD-L1 were stained at the Genetic Pathology Evaluation Centre (Vancouver, BC, Canada) on the Ventana Discovery Ultra autostainer. PD-L1 was stained at the Deeley Research Centre (Victoria, BC, Canada) [ 36 ]. Stained slides were scanned using a Leica Aperio AT2 scanner (Leica Biosystems, Concord, Canada).…”
Section: Methodsmentioning
confidence: 99%